Pemberdayaan Pasien Tuberkulosis Paru dalam Penanganan Penyakit Tuberkulosis di Rumah pada wilayah kerja Puskesmas Kampung Bugis Tahun 2024 - Daniati, Meisa; Romalina, Romalina; Suriani, Yas (SEGANTANG LADA : JURNAL PENGABDIAN KESEHATAN, 2025)
Indonesia is currently facing a double burden of disease, namely communicable and non-communicable diseases. To address this issue, the Ministry of Health (Kemenkes) has initiated a health transformation through six pillars, which are priority programs of the Ministry of Health of the Republic of Indonesia. Various efforts have also been made to reduce the incidence of Pulmonary Tuberculosis (Pulmonary TB) in the working area of Puskesmas Kampung Bugis. However, the activities carried out have not been optimal in reducing the number of Pulmonary TB cases in Tanjungpinang City, especially in the working area of Puskesmas Kampung Bugis. Therefore, there is a need for Community Empowerment, particularly of TB patients, in the management of Pulmonary Tuberculosis at home in the Puskesmas Kampung area of Tanjungpinang City in 2024. The objective of this community service activity is to provide education to the community, especially TB patients, in managing TB disease at home. The method of this community service activity involves health promotion on TB treatment efforts and prevention of TB transmission, which is carried out routinely through the direct delivery of material to the community, especially TB patients, using booklets/leaflets. The activity was held at the Kampung Bugis Health Center on October 2 and 20, 2024. The results showed that the average knowledge score before the education session was 70.5, while after the education session, it increased to 85.3. The conclusion is that there was an increase in the knowledge of Pulmonary TB patients in managing Pulmonary TB at home. Educational activities for Pulmonary TB patients, whether conducted by community health workers or health professionals, should be provided regularly so that pulmonary disease can be controlled in the community.